Incidence and outcome of immune checkpoint-induced pneumonitis in oncology patients with history of pulmonary disease - Allen, Emily; Umoru, Godsfavour; Ajewole, Veronica; Bernicker, Eric (Frontiers in Oncology, 2023)
Background: Immune checkpoint-induced pneumonitis (ICIP) is one of the most fatal adverse events caused by immune checkpoint inhibitors (ICI) and accounts for 35% of anti-PD-[L]1-related deaths. Risk factors including thoracic radiation and use of EGFR tyrosine kinase inhibitors have been identified as contributors to ICIP development. However, there has been very limited information on obstructive pulmonary disease as a risk factor. Objective: The purpose of this study is to evaluate the incidence and management of ICIP in a cohort of patients with pre-existing obstructive pulmonary disease. Methods: This retrospective, descriptive study, includes data from 139 patients between January 1, 2017 and August 31, 2022. Patients included were adult patients 18 years or older, received at least 2 cycles of an immune checkpoint inhibitor, and had a history of an obstructive pulmonary disorder prior to administration. Patients were excluded if they had literature-established risk factors for pneumonitis. Results: The incidence of ICIP was 7.19% (10 out of 139 patients). From a management perspective, 90% of patients had immunotherapy held, 40% received oral steroids, and 70% received intravenous steroids at the time of ICIP identification. After receiving treatment for the initial episode of ICIP, 6 patients restarted immunotherapy and 3 (50%) subsequently experienced a recurrent episode. One patient experienced grade 4 ICIP event and subsequently died from respiratory failure attributed to ICIP.These findings indicate that a pre-existing history of an obstructive pulmonary disorder may be a risk factor for the development of ICIP and subsequent recurrence of ICIP when rechallenged.